2015
DOI: 10.1021/acs.jpcc.5b01264
|View full text |Cite
|
Sign up to set email alerts
|

Deep and Shallow TiO2 Gap States on Cleaved Anatase Single Crystal (101) Surfaces, Nanocrystalline Anatase Films, and ALD Titania Ante and Post Annealing

Abstract: Using photoelectron spectroscopy (PES), deep (around 1.2 eV below Fermi level) and shallow (around 0.2 eV below Fermi level) gap states are investigated in differently prepared TiO 2 samples: In situ cleaved single anatase crystal TiO 2 (101) surface, sintered slurry of nanocrystalline anatase, amorphous atomic layer deposited (ALD) titania, and nanocrystalline anatase transformed by annealing from ALD titania. Deep gap states are generally attributed to under-coordinated Ti atoms due to oxygen defects. The or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
53
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 50 publications
4
53
0
Order By: Relevance
“…In addition to these impurity levels, the hybridization between V‐N, also confirm by XPS causes further narrowing in band gap of V–N‐codoped TiO 2 . In xV4N, the increase in V concentration creates the oxygen vacancies, as confirmed by XPS and XRD results, which are known to form deep levels at 1.0–1.2 eV below the CBM in band gap . Indeed, this oxygen vacancy is responsible for reduction of band gap in addition to the isolated V 4+ ‐based impurities state and being more efficient with increasing concentration of V in codoped TiO 2 .…”
Section: Resultsmentioning
confidence: 69%
“…In addition to these impurity levels, the hybridization between V‐N, also confirm by XPS causes further narrowing in band gap of V–N‐codoped TiO 2 . In xV4N, the increase in V concentration creates the oxygen vacancies, as confirmed by XPS and XRD results, which are known to form deep levels at 1.0–1.2 eV below the CBM in band gap . Indeed, this oxygen vacancy is responsible for reduction of band gap in addition to the isolated V 4+ ‐based impurities state and being more efficient with increasing concentration of V in codoped TiO 2 .…”
Section: Resultsmentioning
confidence: 69%
“…UP spectra are usually more sensitive to surface defects than XP spectra, which is mostly due to the higher surface sensitivity of UPS and the higher intensities. It is accepted that the so-called band gap surface states would form due to occupied Ti 3d states (Ti 3+ ) near the O vacancy sites on the surface, but also due to Ti 3+ interstitials in the subsurface region [4,11,18,63,64]. It is clear from Figure 4 that all sputtered TiO 2 surfaces show the well-known Ti 3d 1 emission lines in the band gap region.…”
Section: Resultsmentioning
confidence: 95%
“…In 2008 Yang et al [7] synthesized anatase single crystals with 47% of the minority (001) facet via a hydrothermal route employing fluoric acid. This successful synthesis has surged further fundamental investigations of both anatase (101) and (001) facets [8][9][10][11]. However, although the electronic structure of anatase bulk and surfaces including band gaps and surface states are well known due a wide range of experimental and theoretical studies using complementary techniques, particularly using electron spectroscopy (see e.g., [11][12][13][14][15][16][17][18][19][20][21]), the surface potentials-Fermi level position, work function and ionization potential-have not yet been studied systematically.…”
Section: Introductionmentioning
confidence: 99%
“…However there are still some unresolved issues with Leaky TiO 2 such as exactly how charge conducts through the TiO 2 . Both DFT calculations 160 and experimental results 161 have shown that oxygen vacancies can allow for deep level trap sites as those found in the Leaky TiO 2 . However calculations by Lewerenz show that the charge transfer was probably not due to a Poole-Frenkel type mechanism.…”
Section: One Of the Mor E Interesting Follow Up Work On The Leaky Timentioning
confidence: 95%